(untitled) (Baghdad Science Journal, 2008)
Five N-substituted acrylamides were prepared by reaction of substituted aromatic primary amines with acryloyl chloride in the presence of triethyl amine. The synthesized acrylamides were allowed to introduce copolymerization reaction with three vinylic monomers including acrylonitrile, methyl acrylate and methyl methacrylate respectively to obtain eleven new copolymers having different physical properties which may used in different applications.